2022
DOI: 10.3390/robotics11050092
|View full text |Cite
|
Sign up to set email alerts
|

Social Robots Outdo the Not-So-Social Media for Self-Disclosure: Safe Machines Preferred to Unsafe Humans?

Abstract: COVID-19 may not be a ‘youth disease’ but it nevertheless impacts the life of young people dramatically, loneliness and a negative mood being an unexpected additional pandemic. Many young people rely on social media for their feeling of connectedness with others. However, social media is suggested to have many negative effects on people’s anxiety. Instead of self-disclosing to others, design may develop alternatives to employ social robots for self-disclosure. In a follow-up on earlier work, we report on a lab… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…Previous studies have reported that people in a bad mood benefited more from disclosing to a robot than participating in writing disclosures in a journal [70] or on social media [77]. Another good example is affect labelling, a simple and implicit emotional regulation technique aimed at explicitly expressing emotions, or in other words-putting feelings into words [78].…”
Section: Using Self-disclosure For a Social Robotic Intervention To S...mentioning
confidence: 99%
“…Previous studies have reported that people in a bad mood benefited more from disclosing to a robot than participating in writing disclosures in a journal [70] or on social media [77]. Another good example is affect labelling, a simple and implicit emotional regulation technique aimed at explicitly expressing emotions, or in other words-putting feelings into words [78].…”
Section: Using Self-disclosure For a Social Robotic Intervention To S...mentioning
confidence: 99%
“…For example, James Pennebaker writing disclosure paradigm [70,71] helps people to facilitate their emotions when writing about their own experiences. Interestingly, previous studies found that people in bad mood benefited more from disclosing to a robot than participating in writing disclosure using a journal [65] or on social media [72]. Another good example is affect labelling, a simple and implicit emotional regulation technique aimed at explicitly expressing emotions, or in other words -putting feelings into words [73].…”
Section: Using Self-disclosure For Social Robotic Interventionmentioning
confidence: 99%
“…An extension to the study address also the gratification of anonymity when self-disclosing to robots, showing that self-disclosing to a robot was also more effective for those in a negative mood than self-disclosing on social media (123). Early work by (124) shows that in a sample of 44 students, participants were less embarrassed when interacting with a "technical box" than with a social robot "iCat" (Phillips) in medical settings asking participants to undress and disclose relevant personal information (e.g., their weight).…”
Section: Anonymity and Rapport In Interactions With Social Robotsmentioning
confidence: 99%